Decline of hippocampal stress reactivity and neuronal ensemble coherence in a mouse model of depression. (May 2016) - Law, Jade; Ibarguen-Vargas, Yadira; Belzung, Catherine; Surget, Alexandre
Highlights: The hippocampus reacts to stress by adjusting neuronal ensemble activations. A mouse model of depression (UCMS) degrades hippocampal reactivity to stress. UCMS decorrelates activity of cell ensembles between CA3/DG hippocampal subfields. Antidepressant treatment reverses the UCMS effects on stress reactivity. Differences along the dorsoventral axis of the hippocampus are evidenced. Abstract: Dysregulations of stress systems, especially the hypothalamo–pituitary–adrenal (HPA) axis, have been commonly reported in major depression. Consistent results emphasized the role of the hippocampus in regulating stress systems and restoring an operative control on HPA axis following antidepressant treatments. However, very little is known about how the hippocampus integrates stress-related information and reacts to stressors beforehand. We therefore aimed to assess activations of hippocampal neuronal ensembles during stress-related experiences and evaluated the effects of a mouse model of depression, the Unpredictable Chronic Mild Stress (UCMS), and an antidepressant treatment (fluoxetine, 20 mg kg −1 day −1, ip) in BALB/cByJ mice. The UCMS induced a depression-like syndrome characterized by a reduced weight gain, a progressive deterioration of the coat, an altered stress-coping strategy in behavioural tests and HPA axis dysregulations. Chronic fluoxetine had no effect in control non-stressed mice per se but reversed the syndrome induced by the UCMS, including an improvement of the HPA-system alterations. Neuronal activation was then assessed by immediate early-gene (c-fos) expression in different subfields of the CA3 and dentate gyrus (DG) along the dorso–ventral axis of the hippocampus, as they can support different computational functions. Our results showed that the hippocampus reacts to stressors by adjusting activations of cell ensembles. A pre-treatment with dexamethasone (DEX), a glucocorticoid receptor (GR) agonist that produced a delayed inhibition of the HPA axis activity, reduced novelty-related activations in the proximal CA3 (CA3c) and the DG of the dorsal hippocampus. All these effects were compromised by the UCMS, particularly by altering activation coherences within the dorsal CA3–DG network, but were rescued by chronic fluoxetine. Our study indicates therefore that variations of CA3–DG cell ensemble activation may contribute to stress integration in the hippocampus and that dysfunctions of this process may foster HPA-system dysregulations and depression-related states. It suggests that pharmacological interventions aiming to consolidate CA3–DG neural network might improve stress reactivity and possibly benefit to patients with major depression.